Quality Assessment of Clinical Practice Guidelines for Asthma Management Using the AGREE II Tool - Magdalena Zielińska; Marta Andrzejewska; Zuzanna Grunwald; Wioleta Opieka; Tomasz Hermanowski; Magdalena Woźniak (Polish Pharmaceutical Society, 2023)
Subject of the study Clinical practice guidelines are an effective strategy for optimizing health care by promoting evidence-based recommendations. Appropriate methodology and a rigorous strategy when formulating the recommendations of clinical guidelines has a significant impact on their quality, reliability and ability to be effectively implemented in practice. Purpose of the study The purpose of our study was to assess the quality of clinical practice guidelines for asthma management using the AGREE II tool. The analysis compared the quality of Polish clinical guidelines with those from other countries and international organizations. Nine guidelines were evaluated: Management of Asthma Exacerbations in Adults - Guidelines for General Practitioners (author: Supreme Medical Council, Poland), Global Strategy for Asthma Management and Prevention (author: The Global Initiative for Asthma (GINA)), Asthma and Respiratory Foundation NZ Adolescent and Adult Asthma Guidelines 2020: a quick reference guide (author: Asthma and Respiratory Foundation New Zealand), Australian Asthma Handbook V2.0 (author: National Asthma Council Australia), National Clinical Guideline: The Diagnosis and Management of Asthma in Adults V2. 1 (author: Ministry of Public Health Qatar), SIGN 158 British guideline on the management of asthma (author: Scottish Intercollegiate Guidelines Network (SIGN) British Thoracic Society), Management of Asthma in Adults (author: Malaysian Health Technology Assessment Section (MaHTAS)), Asthma: diagnosis, monitoring and chronic asthma management (author: National Institute for Health and Care Excellence (NICE)), and The Spanish Guideline on the Management of Asthma (author: Guía Española para el Manejo del Asma (GEMA)). Results The highest scored domains were transparency and presentation of recommendations (all guidelines scored 100% or close to 100%), guideline scope and purpose, and editorial independence. The domains that scored lowest were in the areas of stakeholder engagement and applicability (79.3% and 69.2%, respectively). The largest differences were observed in the area of editorial independence, ranging from 100% (the maximum possible score) to 16.7%. The guidelines developed by the National Institute for Health and Care Excellence and the Scottish Intercollegiate Guidelines Network received the highest overall score. The Polish guidelines received the maximum number of points in areas related to scope and purpose, transparency and presentation, and editorial independence. Conclusions A properly conducted guideline development process, including the involvement of experts and adherence to methodological standards, results in high-quality clinical practice guidelines. High-quality clinical practice guidelines can be used as tools to support clinical decision-making, however, guideline authors should pay special attention to the applicability of guidelines in practice and the involvement of all stakeholders. To improve the process of guideline development and patient access to the newest therapies, it is also important to consider the synergies between the recommendations in clinical practice guidelines and health technology assessment reports.